2014
DOI: 10.1111/pce.12425
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Rubisco and its regulation for greater resource use efficiency

Abstract: Rubisco catalyses the carboxylation of ribulose-1,5-bisphosphate (RuBP), enabling net CO2 assimilation in photosynthesis. The properties and regulation of Rubisco are not optimal for biomass production in current and projected future environments. Rubisco is relatively inefficient, and large amounts of the enzyme are needed to support photosynthesis, requiring large investments in nitrogen. The competing oxygenation of RuBP by Rubisco decreases photosynthetic efficiency. Additionally, Rubisco is inhibited by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
264
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 303 publications
(278 citation statements)
references
References 202 publications
9
264
0
5
Order By: Relevance
“…A large number of studies have previously described Rubisco catalysis (for review, see Parry et al, 2007Parry et al, , 2013Whitney et al, 2011b;Carmo-Silva et al, 2015). However, this still represents a very small fraction of known lands plants (approximately 0.2% based on current literature).…”
Section: Discussion Significant Variation In Rubisco Catalysis Amongmentioning
confidence: 99%
See 3 more Smart Citations
“…A large number of studies have previously described Rubisco catalysis (for review, see Parry et al, 2007Parry et al, , 2013Whitney et al, 2011b;Carmo-Silva et al, 2015). However, this still represents a very small fraction of known lands plants (approximately 0.2% based on current literature).…”
Section: Discussion Significant Variation In Rubisco Catalysis Amongmentioning
confidence: 99%
“…Potential unintended effects on assembly could be a factor when mutating residues known to be involved in interactions between the large and small subunits. Careful consideration must also be given to avoiding effects on holoenzyme assembly and compatibility with ancillary proteins or assembly chaperones (Carmo-Silva et al, 2015;Whitney et al, 2015). This presents a promising avenue for future work in model systems, testing these residues either singly or in combination, with previous studies having shown strong potential for modifying Rubisco catalysis with targeted amino acid substitutions (Whitney et al, 2011b).…”
Section: Targeting Improvements Through Mutagenesismentioning
confidence: 99%
See 2 more Smart Citations
“…In a review of resource use efficiency and climate resilience, Carmo-Silva et al [103] noted that a negative relationship between Rubisco activase and Rubisco content could cancel out potential benefits for WUE of additional allocation of N to the latter. At a molecular level, and in the absence of considerations of N, drought downregulates many photosynthesis-related genes, possibly enhancing WUE i and aiding survival via a slowing of growth [104].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%